The Asia-Pacific consensus on ulcerative colitis - Ooi, Choon Jin; Fock, K.M.; Makharia, G.K.; Goh, Khean Lee; Ling, K.L.; Hilmi, I.; Lim, W.C.; Kelvin, T.; Gibson, P.R.; Gearry, R.B.; Ouyang, Q.; Sollano, J.; et al. (Blackwell Publishing, 2010)
Inflammatory bowel disease (IBD) is increasing in many parts of the Asia-Pacific region. There is a need to improve the awareness of IBD and develop diagnostic and management recommendations relevant to the region. This evidence-based consensus focuses on the definition, epidemiology and management of ulcerative colitis (UC) in Asia. A multi-disciplinary group developed the consensus statements, reviewed the relevant literature, and voted on them anonymously using the Delphi method. The finalized statements were reviewed to determine the level of consensus, evidence quality and strength of recommendation. Infectious colitis must be excluded prior to diagnosing UC. Typical histology and macroscopic extent of the disease seen in the West is found in the Asia-Pacific region. Ulcerative colitis is increasing in many parts of Asia with gender distribution and age of diagnosis similar to the West. Extra-intestinal manifestations including primary sclerosing cholangitis are rarer than in the West. Clinical stratification of disease severity guides management. In Japan, leukocytapheresis is a treatment option. Access to biologic agents remains limited due to high cost and concern over opportunistic infections. The high endemic rates of hepatitis B virus infection require stringent screening before initiating immune-suppressive agents. Vaccination and prophylactic therapies should be initiated on a case-by-case basis and in accordance with local practice. Colorectal cancer complicates chronic colitis. A recent increase in UC is reported in the Asia-Pacific region. These consensus statements aim to improve the recognition of UC and assist clinicians in its management with particular relevance to the region.